Impact of upstream landslide on perialpine lake ecosystem: An assessment using multi-temporal satellite data - Villa, Paolo; Bresciani, Mariano; Bolpagni, Rossano; Braga, Federica; Bellingeri, Dario; Giardino, Claudia (The Science of the total environment, 2020)
Monitoring freshwater and wetland systems and their response to stressors of natural or anthropogenic origin is critical for ecosystem conservation. A multi-temporal set of 87 images, acquired by Sentinel-2 satellites over three years (2016–2018), provided quantitative information for assessing the temporal evolution of key ecosystem variables in the perialpine Lake Mezzola (northern Italy), which has suffered from the impacts of a massive landslide that took place upstream of the lake basin in summer 2017. Sentinel-2 derived products revealed an increase in lake turbidity triggered by the landslide that amounted to twice the average values scored in the years preceding and following the event. Hotspots of turbidity within the lake were in particular highlighted. Moreover, both submerged and riparian vegetation showed harmful impacts due to sediment deposition. A partial loss of submerged macrophyte cover was found, with delayed growth and a possible community shift in favor of species adapted to inorganic substrates. Satellite-derived seasonal dynamics showed that exceptional sediment load can overwrite climatic factors in controlling phenology of riparian reed beds, resulting in two consecutive years with shorter than normal growing season and roughly 20% drop in productivity, according to spectral proxies. Compared to 2016, senescence came earlier by around 20 days on average in 2017 season, and green-up was delayed by up to 50 days (20 days, on average) in 2018, following the landslide. The approach presented could be easily implemented for continuous monitoring of similar ecosystems subject to external pressures with periods of high sediment loads. [Display omitted] •Studying response of freshwater systems to stressors is critical for conservation.•Impact of upstream landslide on perialpine lake was assessed with satellite data.•We mapped turbidity, substrate cover and reed seasonal dynamics for 3 years.•We quantified submerged macrophyte changes and riparian reeds productivity loss.•Sentinel-2 data enable operational monitoring of key lake ecosystem parameters.